Studying the Islamic lifestyle and academic success of Russian Muslim students - Abdullah, Zuraidah (HTS teologiese studies, 2022)
The notion of lifestyle has recently attracted the attention of various scholars as a social science concept. For thousands of years, human beings attempted to realise and manage their lifestyles, and governments have tried to influence the lifestyles of their people. Nevertheless, the definition of lifestyle and its conceptualisation is relatively new. Lifestyle means the specific method of living of an individual, group or community. Lifestyles include a set of values, behaviours, moods and tastes that can refer to the interests, opinions, behaviours and behavioural orientations of an individual, group or culture. The Islamic way of life follows a grand plan of behaviour according to which all life is a movement to get closer to God. This plan, however, is dynamic and always demands adjustment. In a desirable religious life, all actions and situations can be called worship. People’s lifestyles and the path they choose for themselves are deeply related to their success in life. Therefore, the present study aimed to evaluate the effect of the Islamic lifestyle on the academic success of Russian Muslim students in 2021. In total, 2000 graduate students of Kazan, Russia were studied in this research. According to the results of mean analysis in SPSS, the academic success of the students who followed the Islamic lifestyle was reported to be higher than the mean level (more than 3 out of 5). Furthermore, according to the Structural Equation Modeling in LESREL, the Islamic lifestyle has a positive significant effect on the students’ academic success (p-value: 0.83; t-value: 7.92).Contribution: Amongst the various factors that can influence students’ academic success, the current research focused on the Islamic lifestyle. The findings of the present study offered a new insight into the relationship between the Islamic lifestyle and academic success in Russia.